The perspective of al-Sunnah al-Nabawiyyah to handle the outbreak of a Pandemic Disease - et. al., Muhammad Masruri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Infectious diseases that have reached the stage of pandemic are dangerous diseases because of the level of invection quickly and spread throughout the world. This disease infects anyone without exception. Although infectious diseases already exist and have been known since the time of the Prophet Muhammad PBUH, but there are still many people who do not understand that the method of the Prophet PBUH is one of the best methods to stop the infection and the chain of pandemic diseases. This article aims to describe some of the methods used by The Prophet while facing the spread of Plague and Leprosy infection in the community. Study of the text and the content of the approach of the Prophet PBUH to handle and stop the infectious diseases that reach pandemic levels. Among the methods are; a ban on entering the affected area and a ban on leaving it, stay at home, be patient and believe in the provisions of Allah SWT, did not meet the patient, keep distance with others, strive to find healing and believing that every disease has a cure, The teachings and guidance of the Prophet SAW is expected as a guide for Muslims when experiencing the outbreak of pandemic disease from time to time.